INTEGRATING INTERCULTURAL COMMUNICATIVE COMPETENCE INTO ENGLISH LANGUAGE TEACHING - Ida Bagus Nyoman Mantra; Anak Agung Putri Maharani; I Kadek Dian Satriawan; Sang Ayu Putu Ichita Dewi; Ni Luh Putu Anggi Widyantari; Ni Made Lovi Arini (International Journal of Multidisciplinary Reseach, 2026)
The increasing importance of English as a worldwide lingua franca requires that learners are prepared with not only linguistic competence but also the capacity to communicate in meaningful ways across different cultural contexts. The present study explores the integration of Intercultural Communicative Competence (ICC) in English Language Teaching (ELT) by examining its theoretical basis, classroom implementation and the perceived advantages and disadvantages. The qualitative study design was used using literature analysis and semi-structured interviews with five selected purposefully English teachers. Data from both sources were analysed thematically for repeating patterns and themes. The findings suggest that ICC is seen by the literature and the teachers participating as an important aspect of successful English language teaching. Teachers used intercultural education through comparative cultural discussions, real multimedia tools, collaborative projects, role-plays and reflective classroom activities. These strategies were believed to contribute to students’ communicative competence, intercultural awareness, critical thinking, learner engagement, and appreciation for cultural diversity. The study identified several challenges for the systematic implementation of ICC, including: examination-oriented curriculum, limited time for teaching, lack of intercultural teaching resources and lack of professional development opportunities for teachers. Research shows that successful implementation includes curriculum support, ongoing teacher training, and culturally responsive teaching. Intercultural competency in English language education helps learners to be ready to interact successfully and appropriately in multicultural academic, social and professional settings, and promotes global citizenship and intercultural awareness.